A concise history of Canada - Conrad, Margaret (Cambridge concise histories, 2022)
"Margaret Conrad's history of Canada begins with a challenge to its readers. What is Canada? What makes up this diverse, complex, and often contested nation-state? What was its founding moment? And who are its people? Drawing on her many years of experience as a scholar, writer, and teacher of Canadian history, Conrad offers astute answers to these difficult questions. Beginning in Canada's deep past with the arrival of its Indigenous peoples, she traces its history through the conquest by Europeans, the American Revolutionary War, and the industrialization of the nineteenth and twentieth centuries, to its prosperous present. As a social historian, Conrad emphasizes the peoples' history: the relationships between Indigenous peoples and settlers, French and English, Catholic and Protestant, rich and poor. She writes of the impact of disease, how women fared in the early colonies, and the social transformations that took place after the Second World War as Canada began to assert itself as an independent nation. It is this grounded approach that drives the narrative and makes for compelling reading. In its final chapters, the author explains the social, economic, and political upheavals that have bedeviled the nation in recent years. Despite its successes and its popularity as a destination for immigrants from across the world, Canada remains a cautious and contested country. This intelligent, concise, and lucid book explains just why that is"-- Provided by publisher.